Flow of a falling liquid curtain into a pool. (25th February 2014) - Kyotoh, Harumichi; Fujita, Kazuki; Nakano, Koichi; Tsuda, Takeaki
Abstract: We investigate the low-Weber-number flow of a liquid curtain bridged between two vertical edge guides and a pool surface. Three flow patterns, namely, steady vertical flow, steady oblique flow, and oscillatory oblique flow, are observed in our experiment. These patterns are caused by the Coanda effect of the jet around the meniscus that is formed in the matching region common to the liquid curtain and the pool surface. Here, the deflection angle of the jet is greater than $90^° $ . The equation describing the motion of the liquid curtain applicable for a finite curtain slope is obtained using the intrinsic coordinate system in which the distance along the curtain is selected as one of the coordinates, and the equation of the meniscus motion is derived by considering the conservation of momentum. The curtain deformations of oblique flows are analysed by generating numerical simulations of these equations, and the simulation results are then compared with experimental results. Also, the period of oscillatory oblique flow is discussed and explained via the response analyses of the curtain, and the result shows that the period of the oscillations is close to that of the most amplified mode of the liquid curtain. Further, the detachment angle of the jet is discussed in relation to the Coanda effect of the jet in the meniscus.